KEPUASAN MASYARAKAT PROVINSI JAMBI TERHADAP PERATURAN DAERAH YANG DIHASILKAN OLEH ANGGOTA DPRD PERIODE 2019-2022 - Lestiany, Tri Endah Karya; ., Burhanuddin; FA, Jalaluddin (Universitas Gorontalo, 2024)
This study aims to determine the level of satisfaction of the Jambi Province community with the regional regulations produced by the members of the Jambi Province Regional House of Representatives (DPRD) for the 2019-2022 period. This research employs both quantitative descriptive and qualitative descriptive approaches. One of the main functions of the DPRD is the legislative function, which holds significant authority in forming regional regulations (Perda). However, when considering the total number of Perda produced by the local government from 2019 to 2022, the perception of their quality remains far from ideal. The results of this study indicate that the people of Jambi Province are satisfied with the regional regulations produced by the DPRD members during the 2019-2022 period. Although the quantity of Perda produced was only 13, there are regulations that, although indirectly, will provide benefits and have an overall impact on general welfare